HEV plant model design methodology for HCU testing on HiLS - Gupta, Sumit; Khan, Md Imran; Sahoo, Tapan (2015 IEEE International Transportation Electrification Conference (ITEC), 2015)
This paper presents the methodology and utility of an HEV plant model using Matlab-Simulink for testing the HCU (Hybrid control Unit) logics in dSPACE Hardware-in-loop environment. It also describes how requirements related to Hybrid Controller testing are addressed using the subject plant model. It further discuss about the requirements for Inputs to hybrid controller that are modeled in close loop environment by modeling all engine and vehicle related signals like vehicle speed, Engine speed, accelerator, brake, clutch, boost pressure, rail pressure, motor torque, battery SOC etc. The paper also describes the ability of model to test the software logics of Hybrid functions like stop start, brake energy regeneration, torque assist etc. It further shows the plant model utility, for HCU calibration and vehicle fuel efficiency simulations in close-loop environment, with better accuracy as compared to conventional vehicle calibration and simulation.